Pendampingan Strategi Pemasaran Digital untuk UMKM Salsa Brownies - Purnama, Ita; Sarina, Sarina; Dwiyanti, Rosa (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2025)
This mentoring aims to increase turnover and expand the market share of Salsa Brownies MSMEs in Bima City and District by leveraging digital technology, particularly social media, which has not been utilised previously. The research method involved four stages of mentoring. The first stage involved surveying MSME locations. The second stage entailed socialising with MSMEs. The third stage assisted in creating Instagram and Facebook social media accounts at MSME locations. The fourth stage was an evaluation of the programme that had been carried out. The results of the assistance showed an increase in the understanding and skills of MSME owners in using social media for promotion. Previously, Salsa Brownies MSMEs relied solely on conventional promotions, but after the training, they began to upload products and interact with potential buyers more actively. This success not only increases the digital capacity of MSMEs but also opens up opportunities to reach a broader market, increase brand awareness, and contribute to local economic growth.